A Comparative Study on the Larvicidal Effect of Ethanol Leaf Extracts of Cymbopogon Citratus (Lemongrass) and Ximenia Americana (Sea Lemon) on Anopheles and Culex Larva (Global Journal of Science Frontier Research, 2022)
Abstract not found
Keywords: cymbopogon citratus; xymenia americana; anopheles; culex; laevae